2013
DOI: 10.1037/a0032922
|View full text |Cite
|
Sign up to set email alerts
|

Spend today, clean tomorrow: Predicting methamphetamine abstinence in a randomized controlled trial.

Abstract: Objective This secondary analysis of data from a randomized controlled trial tested two behavioral economics mechanisms (substitutability and delay discounting) to explain outcomes using contingency management (CM) for methamphetamine dependence. Frequency and purchase type (hedonic/utilitarian and consumable/durable) of CM payments were also examined. Methods 82 methamphetamine-dependent gay/bisexual men randomly assigned to conditions delivering CM received monetary vouchers in exchange for stimulant-negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…Cash incentives were provided to participants at each urine screening visit as an immediate, tangible reinforcement for ATS abstinence. This is consistent with prior research where more frequent receipt of cash incentives earned in CCT was associated with greater odds of abstinence at subsequent urine screening visits (Ling Murtaugh, Krishnamurti, Davis, Reback, & Shoptaw, 2013). Where participants provided a positive urine test for ATS, they did not receive the incentive for that visit or a cash bonus for that week.…”
Section: Methodssupporting
confidence: 91%
“…Cash incentives were provided to participants at each urine screening visit as an immediate, tangible reinforcement for ATS abstinence. This is consistent with prior research where more frequent receipt of cash incentives earned in CCT was associated with greater odds of abstinence at subsequent urine screening visits (Ling Murtaugh, Krishnamurti, Davis, Reback, & Shoptaw, 2013). Where participants provided a positive urine test for ATS, they did not receive the incentive for that visit or a cash bonus for that week.…”
Section: Methodssupporting
confidence: 91%
“…Another option may involve manipulating the way in which rewards are delivered. In controlled secondary data analyses, frequently spending rewards earned in a contingency management schedule (compared to saving for a high‐value good) significantly increased the likelihood that methamphetamine‐dependent individuals would appear at their next clinic visit abstinent from drug .…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…Second, Ling-Murtaugh and colleagues revealed a significant positive association between rates of CM voucher redemption and biomarker-confirmed substance abstinence (Ling-Murtaugh, Krishnamurti, Davis, Reback, Shoptaw 2013), corroborating the existence of an empirical link between substance use and real-life decision making. Results showed that treatment-seeking, substance-dependent gay and bisexual men were more likely to submit clean urine samples if they redeemed their CM vouchers with greater frequency, a result the authors ascribed to the “substitutability” of the rewards offered through voucher redemption.…”
Section: Introductionmentioning
confidence: 82%
“…It is unknown whether results presented here are generalizable to other (e.g., less impacted, treatment seeking) populations. For example, recall that among treatment-seeking, substance-dependent gay and bisexual men, those participants who redeemed their CM vouchers more frequently were more likely to submit clean urine samples (Ling-Murtaugh et al, 2013). Such a result contrasts with the findings presented here and may be due to the aforementioned study participants’ status as treatment-seekers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation